UJI PESTISIDA NABATI DAUN CENGKEH (Syzygium aromaticum L.) UNTUK MENGENDALIKAN HAMA KUTU DAUN (Aphid sp.) PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Sri AlvionitaDjau; Nikmah Musa; Mohamad Lihawa (Percetakan Umi Toaha Makassar, 2022)
This research aimed to determine the test of clove leaf vegetable pesticide in controlling aphids on the shili pepper. This research was conducted in HulawaVilalge, Telaga Sub-district, Gorontalo Regency, Gorontalo Province, using a Randomized Block Design (RAK) method consisten of 4 levels, namely P0 = control, P1 = 5% clove leaf vegetable pesticide concentration, P2 = 10% clove leaf vegetable pesticide concentration, P3 = 15% clove leaf vegetable pesticide concentration. Each treatment was repeated three times so that 12 experimental units (polybags) were obtained. Data were analyzed using the Analysis of Variance (ANOVA) and Least Significant Difference (BNT) at the 5% leave as an advanced test. The result showed that the clove leaf vegetable pesticide affected aphids in mortality, attack intensity, and population. The concentration of 15% clove leaf vegetable pesticide was the most effective in inhibiting the development of aphids and was able to protect chili pepper from aphids.